BEYOND PUNISHMENT: STRATEGI INKLUSIF DAN PEMBERDAYAAN SOSIAL DALAM PEMBERANTASAN KORUPSI - Rahmat Angga Dwi Putra; Adhe Ismail Ananda; Tomi Agi Fratama (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Corruption eradication in Indonesia remains strongly shaped by a repressive approach centered on investigation, prosecution, imprisonment, fines, and asset recovery. Although this approach is essential for criminal accountability, recent empirical indicators show that intensive law enforcement has not fully produced a sustainable integrity system. KPK enforcement statistics, Indonesia’s 2024 Corruption Perception Index score of 37/100, and ICW’s 2024 corruption monitoring report indicate that corruption persists as a structural, institutional, and cultural problem. This article examines the limitations of a punishment-oriented approach and proposes an integrity ecosystem approach based on social empowerment, public participation, and cross-sector collaboration. This research uses normative legal research with statutory, conceptual, and comparative approaches. The comparative scope is limited to Georgia and Finland. Georgia is analyzed through bureaucratic reform, public service transparency, digital monitoring, and civil society participation, while Finland is examined through integrity education, public trust, institutional accountability, and legal culture. The article argues that corruption eradication should not weaken criminal punishment, but should place punishment within a broader policy architecture. Social reintegration and restorative sanctions are positioned as complementary mechanisms, not substitutes for criminal liability. They include asset recovery, restitution of state losses, restrictions on public office, mandatory integrity education, anti-corruption social work, and post-sentencing monitoring. The article concludes that sustainable anti-corruption policy requires a shift from mere punishment to an integrity ecosystem involving the state, civil society, academia, media, and the private sector